Frontalis Muscle Strength Calculation Based On 3D Image Using Gray Level Co-occurrence Matrix (GLCM) and Confidence Interval - Hardianto Wibowo; Eko Mulyanto Yuniarno; Aris Widayati; Mauridhi Hery Purnomo (Universitas Ahmad Dahlan, 2018)
One of the effects of the disorders of nervus VII (n. Facialis) is the damage of facial muscle. The research is needed in order to detect or as the therapies aids on the damage of the VII nerve by measuring the strength of maximum contraction, to help a therapy or detect the damage which caused by the decreasing of the VII nerve function. These measurement is taken from the difference on myofibrin when the contractions, because when the contraction happen, the myofibrin will distend and the difference can be detected as the strength of contraction. From the result of the comparison, EMG with the test result is the shift muscle movement amount of 1.367 up to 4.460. The mean value of rest muscle is in the range of 0.635 with interval at+0.463, on the move muscles the mean value of the muscle moving is in the range of 3,563 with interval at+1,069. This test is linear with the data EMG.